EFEKTIVITAS PROBLEM BASED LEARNING TERINTEGRASI STEM DALAM MENINGKATKAN LITERASI NUMERASI DAN PEMAHAMAN KOGNITIF SISWA SEKOLAH DASAR: STUDI QUASI-EKSPERIMEN - Astuti, Eny; Sumarno, Sumarno; Dwijayanti, Ida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the effectiveness of a STEM-integrated Problem-Based Learning (PBL) model in improving elementary school students’ numeracy literacy skills and cognitive learning outcomes (understanding). A quasi-experimental design with a nonequivalent control group was used, involving two groups: an experimental group (PBL-STEM) and a control group (conventional instruction). Both groups took pre- and post-tests to measure numeracy literacy and mathematical comprehension. Data analysis included N-Gain scores, tests of normality and homogeneity, and mean-difference tests (ANOVA and t-test). The results showed that the experimental group’s average N-Gain for numeracy literacy was 41.67%, higher than the control group’s 28.57%, but this difference was not statistically significant (F = 1.799; p = 0.195). In contrast, the increase in cognitive learning outcomes in the experimental group (N-Gain = 33.64%) was significantly greater than in the control group (N-Gain = 13.98%) (t = 2.266; p = 0.035; 95% CI [1.560, 37.757]). Moreover, the mastery rate (minimum competency score = 70) for both numeracy literacy and comprehension reached 100% in the experimental class, compared to 71% in the control class. These findings confirm that PBL-STEM effectively strengthens conceptual understanding and ensures students meet minimum competency, although further optimization of intervention duration and resource support is needed to achieve significant gains in numeracy literacy. It is recommended that PBL-STEM implementation be accompanied by teacher training and adequate supporting facilities to enhance its impact on numeracy literacy.